Diazoalkane addition reaction on the fullerene dimer C120O and characterization of the resulting mono-adduct. - Uwe Ritter; Markus Reinmöller; Lars Weber (Carbon: Science and Technology, 2008)
A mono-adduct of the fullerene dimer C120O was prepared via a diazoalkane addition reaction to obtain rod-like analogue of[60]PCBM opening the possibility to make photovoltaic and photosensitive layers of supra-molecular and anisotropic order.The mono-adduct was obtained as a mixture containing five isomers. The structure of the mono-adduct was verified bymass-, IR-, and 1H-NMR-spectroscopies. The mono-adduct is readily soluble in common fullerene solvents and shows abroader and stronger optical absorption than [60]PCBM. The mono-adduct features a similar acceptor strength as [60]PCBMand [70]PCBM, is stable in air below 150 °C and in nitrogen below 500 °C. The mono-adduct is expected to be a valuablematerial for photovoltaic and photosensitive applications.